Linguistic Landscape in Palangka Raya City: Patterns, Roles, and Functions - Sari, M. Alpian; Luardini, Maria Arina; Perdana, Indra (IKIP Siliwangi, 2025)
The linguistic landscape refers to the visibility and presence of languages in public spaces. The use of linguistic landscape in public spaces has patterns, roles, and functions. Language plays a vital role in human life because language is a means of communication in everyday life. This study aimed to describe the linguistic landscapes that appeared in public spaces qualitatively. The researcher collected the data through observations and photo documentation. The research data and information obtained showed that the linguistic landscape in Palangka Raya plays a crucial role. The use of English in Palangka Raya can be easily found in public spaces, whether in the form of words, phrases, and sentences, monolingual (English), bilingual (English-Indonesian), or multilingual. This research also reported that the roles of the linguistic landscape found in Palangka Raya are identity representation and social representation. As well as the function of the linguistic landscape itself, the result of this study showed that the function of the linguistic landscape in the public space of Palangka Raya is informative uses and interactive uses. The use of English in Palangka Raya occurs because English is associated with globalization, language and cultural transformation towards modernity, high fashion, and personal freedom.